Kesiapan Kompetensi Pelaku Jasa Konstruksi dalam Menghadapi e-Procurement di Wilayah Terpencil - Soltan Takdir; Girinius Wenda; Fera Auliyati (Jaanur Elbarik Indonesia, 2025)
This study analyzes the readiness level of construction service companies in Jayawijaya Regency to implement e-Procurement. A quantitative descriptive method was used, focusing on three key indicators: knowledge, skills, and attitude. The results show that the overall readiness level is categorized as